2015
DOI: 10.1039/c5ra08299d
|View full text |Cite
|
Sign up to set email alerts
|

A review of upgrading heavy oils with supercritical fluids

Abstract: Due to the decrease in light crude oil and the ever-increasing demand for the upgrading of heavy oils, the development of new heavy oil processing technology has been attracting wide attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 87 publications
(130 reference statements)
0
33
0
Order By: Relevance
“…This is the consequence of the intensification of cracking reactions. As is indicated that the HTU process is dominated by free-radical reactions [36]. With the increase of temperature and pressure in NC and SC conditions, a large amount of C−N and C−S bonds were cleaved, which is partly evidenced by the significant reduction in nitrogen and sulphur content (Section 3.3.2).…”
Section: Changes In Sara Fractionsmentioning
confidence: 95%
“…This is the consequence of the intensification of cracking reactions. As is indicated that the HTU process is dominated by free-radical reactions [36]. With the increase of temperature and pressure in NC and SC conditions, a large amount of C−N and C−S bonds were cleaved, which is partly evidenced by the significant reduction in nitrogen and sulphur content (Section 3.3.2).…”
Section: Changes In Sara Fractionsmentioning
confidence: 95%
“…Furthermore, water itself can act either as a catalyst or reactant, reducing the hydrogen requirement of downstream processes. 13 Previous studies 5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] have established the potential of SCW treatment to upgrade model compounds and fractions of crude oil. When it comes to crude oil, most literature studies report the effects of SCW treatment on the bulk properties 14,15,18 and only a few studies describe changes at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have established the potential of SCW treatment to upgrade model compounds and fractions of crude oil. When it comes to crude oil, most literature studies report the effects of SCW treatment on the bulk properties and only a few studies describe changes at the molecular level .…”
Section: Introductionmentioning
confidence: 99%
“…Supercritical fluid (SCF) has attracted considerable attention as a density-tunable medium that enables the control of physicochemical properties such as permittivity, viscosity, and thermal conductivity. Supercritical carbon dioxide (scCO 2 ) has been most extensively utilized as a solvent for chemical and physical processes because of its low critical point ( T c = 304.1 K, P c = 7.4 MPa), nontoxicity, and its cost-effectiveness as a fluid. High solubility of the solute in scCO 2 is important for the efficient use of scCO 2 in chemical and physical processes. , For example, carbonyl compounds exhibit high solubility in scCO 2 . In particular, esters and ketones have served as the most popular carbonyl compounds utilized in scCO 2 . To understand the mechanism of both their high solubility and the intermolecular interactions in scCO 2 , several experimental and theoretical investigations have been reported. Fink et al observed a 5-fold increase in solubility by attachment of a carbonyl group onto a solute molecule . Kazarian et al used infrared spectroscopy to observe large interaction between CO 2 and the carbonyl group .…”
Section: Introductionmentioning
confidence: 99%